Analisis Karakteristik Permasalahan Kesehatan Mental Remaja Disabilitas Intelektual di SLB Negeri 1 Padang - Putri Julia; Setia Budi; Johandri Taufan; Mardhatillah Zulpiani (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aimed to analyze the characteristics of mental health problems among adolescents with intellectual disabilities at SLB Negeri 1 Padang. A qualitative approach with a case study design was employed. Data were collected through observations, semi-structured interviews, and documentation involving five informants, namely the principal, two vice principals, and two classroom teachers selected using purposive sampling. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña through data condensation, data display, and conclusion drawing and verification. The findings revealed that adolescents with intellectual disabilities experienced difficulties in emotional regulation, mood instability, social withdrawal, low self-confidence, difficulties in adapting to new environments, and limitations in expressing their feelings and personal needs. These problems were influenced by adaptive abilities, social experiences, family support, and the school environment. The findings also indicate that each adolescent demonstrates different mental health characteristics, requiring individualized educational and psychosocial support. This study concludes that collaboration among schools, families, and the social environment plays an essential role in promoting the psychological well-being of adolescents with intellectual disabilities and provides important implications for developing more responsive school-based mental health support services.